The Effects of Security and Service Quality on Customer Satisfaction: An Analysis of the Wondr by BNI Users - Meisi Asasa; Maulana Agung Pratama; Hartono (Cita konsultindo, 2026)
The purpose of this study is to evaluate how customer catisfaction is impacted by service security and quality with Wondr by BNI services among business administration students at the University of Lampung. Business development has experienced rapid growth. The method used was an integrative quantitative approach, with a sample of 293 respondents, business administration students who had used the Wondr by BNI application. Data collection was conducted utilizing a The Likert scale questionnaire and examined using multiple linear regression The study's conclusions show a significant and substantial impact on satisfaction with the application. Service quality influences usage, while security provides concrete verification of the commitment to protecting user privacy. Practically, this study provides managerial implications for BNI's marketing strategy to increase the loyalty of environmentally conscious consumers in emerging markets.